PHYTOCHEMISTRY PROFILE, EFFICACY, AND SAFETY OF GREEN TEA (Camellia sinensis (L.) Kuntze) FOR BREAST CANCER CHEMOPREVENTION: A SYSTEMATIC REVIEW - Dwi Hartanti; Siti Rofida (Jurnal Tumbuhan Obat Indonesia, 2021)
ABSTRACT The consumption of tea (Camellia sinensis (L.) Kuntze), mainly green tea, is famous for various health benefits. This review summarizes the potential use of green tea and epigallocatechin gallate (EGCG) for breast cancer chemoprevention. The data were retrieved from the online publication on the Pubmed database and covered the phytochemistry, preclinical study, and clinical trial of green tea related to its use as a breast cancer chemopreventive agent. Catechins, particularly EGCG, are the chemopreventive bioactive constituents of green tea. Preclinical studies demonstrated that the anti-proliferative and induction of apoptosis potentials of green tea are mediated through several different mechanisms. However, no association between green tea intake and a lowered breast cancer risk in human studies, but it might be favorable for secondary cancer prevention. Keywords: green tea, epigallocatechin gallate, chemopreventive, breast cancer. ABSTRAK Konsumsi teh (Camellia sinensis (L.) Kuntze), terutama teh hijau, terkenal dengan berbagai manfaat kesehatannya. Ulasan ini merangkum potensi penggunaan teh hijau dan epigallocatechin gallate (EGCG) untuk kemoprevensi kanker payudara. Data diambil dari publikasi online di database Pubmed dan mencakup fitokimia, studi praklinis, dan uji klinis teh hijau terkait dengan penggunaannya sebagai agen kemopreventif kanker payudara. Katekin, terutama EGCG, adalah konstituen bioaktif kemopreventif teh hijau. Studi praklinis menunjukkan bahwa anti-proliferatif dan induksi potensi apoptosis teh hijau dimediasi melalui beberapa mekanisme yang berbeda. Namun, tidak ada hubungan antara asupan teh hijau dan penurunan risiko kanker payudara dalam penelitian pada manusia, tetapi mungkin menguntungkan untuk pencegahan kanker sekunder. Kata kunci: teh hijau, epigallocatechin gallate, kemopreventif, kanker payudara.